Aplikasi Pencarian Informasi Pondok Pesantren Se-Indonesia Dengan Algoritma Zhu-Takaoka Berbasis Android - Adha, Muhammad Hudan; Sembiring, Abdul Sani; Hutabarat, Hukendik (Building of Informatics, Technology and Science (BITS), 2020)
Islamic boarding school is a dormitory-based Islamic religious education institution. Until now, Islamic boarding schools have had the same level as junior and senior high schools. So that many of the parents want their children to go to a pesantren. However, some parents lack information from the pesantren. Such as address, activities, and so on. One way to get this information is by browsing on the internet. But that is only part of it. Because most Islamic boarding schools don't have official websites. And also for prospective Islamic boarding school graduates who want to complete their final obligations by serving at other Islamic boarding schools, it will also be difficult to find information about Islamic boarding schools, given that they are not allowed to bring electronic items to Pesantren. To overcome the above problems the author wants to design an android-based application by implementing the zhu-takaoka algorithm. Zhu-Takaoka algorithm is one string matching algorithm that can do word search with a lot of shifts with an array of 2 (two) dimensions